Oesophageal protection during AF ablation: real world registry data and mechanisms behind the therapeutic effect of tissue cooling. (19th May 2022) - Leung, L; Akhtar, Z; Bajpai, A; Li, A; Sohal, M; Norman, M; Kaba, R; Al-Subaie, N; Louis-Auguste, J; Hayat, J; Zuberi, Z; Gallagher, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Oesophageal protection using a dedicated device to provide controlled active thermal protection of the oesophagus during atrial fibrillation ablation has been shown to be effective at reducing endoscopically detected oesophageal lesions. Real world registry data of this device and established evidence on the effect of cooling on localized tissue after thermal injury have been under review. Purpose: To determine the safety of an oesophageal temperature control device by a review of real-world registry data on its clinical use during catheter ablation procedures and to clarify basic mechanisms of its therapeutic action by a literature review of scientific studies on cooling in the context of thermal injury. Methods: The United States Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE), FDA Medical and Radiation Emitting Device Recalls, the Medicines and Healthcare products Regulatory Agency (MHRA) Medical Device Alerts and SwissMedic records of Field Safety Corrective Actions (FSCA) databases were reviewed for any device-related adverse events. A systematic literature review was conducted to clarify the findings from studies investigating the physiological processes behind the therapeutic effect of cooling after tissue thermal injury. Results: Of over 20, 000 oesophageal temperature control devices clinically used, 7976 were recorded as having been used for the purpose of oesophageal protection during left atrial catheter ablations. No adverse events occurred related to its use during left atrial catheter ablations. No case of clinically significant oesophageal injury was reported in a patient who had been protected by the oesophageal temperature control device. 208 research articles retrieved from PubMed and MEDLINE that met the search criteria were reviewed. The common finding in all the studies was that cooling had an anti-inflammatory and restorative effect via modulation of several immune-mediated pathways, local cellular function and genetic expression. Conclusions: There have been no adverse events reported to date in real world clinical use of an oesophageal temperature control device during left atrial catheter ablations, for the purpose of active thermal protection. Literature review data suggests that there are complex biophysical and cellular effects from cooling that leads to its therapeutic effect but further work is required to define the mechanisms of action of thermal protection in this specific context.